Leveraging Scopus AI for Exploring the Entrepreneurial Competency Framework (EntreComp) - Idris, Nadzimah; Razalli, Abdul Rahim; Mohd Jamil, Mohd Ridhuan; Ab Malik, Zulezwan (International Business Education Journal, 2025)
Difficulties in understanding the study model or framework are often a significant challenge for most postgraduate students, which can create the perception that postgraduate-level studies are particularly difficult. Now, along with the advancement of technology, applications that utilize assistance from artificial intelligence (AI) are more commonly referred to simply as ’artificial intelligence’ or ’AI’ have made the learning process easier and clearer. This study aims to explore how Scopus AI aids postgraduate students’ understanding of the Entrepreneurial Competency framework (EntreComp). An autoethnography qualitative research design is utilized, with the researcher acting as the primary instrument for data collection and analysis. The analysis results indicate that five key elements in the Scopus AI display facilitate information exploration related to the Entrepreneurial Competency framework (EntreComp). These elements are summary, expanded summary, concept map, topic expert, and go deeper. Scopus AI’s user-friendly display feature has made it easier for postgraduate students to get accurate information quickly and easily based on the Scopus database. These elements help students easily access and understand complex information, leading to better learning outcomes. In summary, Scopus AI effectively aids postgraduate students in grasping the Entrepreneurial Competency (EntreComp) framework. The principal implications of employing this tool within the context of postgraduate education in the contemporary technological environment include enhanced accessibility and a comprehensive understanding of the framework. These factors contribute to a more effective and interactive, data-driven learning process.